ANALISIS KINERJA GURU MATA PELAJARAN BIOLOGI DALAM IMPLEMENTASI KURIKULUM 2013 - Nurul Adzierah; Nur Hikmatang; Astiana Astiana (JURNAL MAPPESONA, 2020)
This study aims to determine the performance of biology subject teachers in the implementation of the 2013 curriculum. The performance The teacher is seen from the planning of learning, the implementation of learning, and assessment learning and inhibiting and supporting factors in planning, implementing and evaluating learning. This research is a descriptive study with a qualitative approach. The results showed that: (1) the performance of biology subject teachers in planning curriculum learning in 2013 was good (2) the performance of biology subject teachers in implementing the 2013 curriculum learning was good (3) the performance of biology subject teachers in evaluating 2013 curriculum learning was good (4) The inhibiting factors experienced by biology subject teachers apply the 2013 curriculum, namely the time of making lesson plans, the activeness of students. Then the supporting factor is that the teacher has basically participated in the 2013 curriculum training, the teacher has a syllabus grip so that it makes it easier for the teacher make lesson plans, teachers and students have a handbook, the use of media and learning methods in accordance with the material, the presence of students in each subject matter and assessment rubrics that become a benchmark in assessing students.